Relationship Between Vegetation Greenness (NDVI) and Land Surface Temperature Across Land Cover Types in Ciwidey Sub-Watershed (1990–2020) - Syabila, Syal; Marko, Kuswantoro; Hernina, Revi (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2026)
Land cover change significantly influences vegetation greenness and land surface temperature (LST), particularly in upstream watershed regions experiencing rapid development. This study aims to analyze changes in vegetation greenness (NDVI), land surface temperature, and their relationship across different land cover types in the Ciwidey Sub-Watershed, Bandung Regency, during 1990–2020. Landsat 5 TM and Landsat 8 OLI images (Path/Row 122/65) acquired in July 1990, 2005, and 2020 were processed using radiometric correction, supervised classification (Maximum Likelihood), NDVI extraction, and mono-window LST algorithm. Land cover classification accuracy was assessed using confusion matrix analysis. Linear regression was applied to evaluate the relationship between NDVI and LST. Results indicate a decline in high vegetation greenness areas and an increase in very low greenness and non-vegetated areas, particularly in built-up land and mixed gardens. Surface temperature shows a consistent upward trend, with dominant temperature classes shifting from 19–21°C (1990–2005) to 22–24°C (2020). Regression analysis reveals a strong negative relationship between NDVI and LST in all observed years (1990: y = -15.113x + 20.683; 2005: y = -14.313x + 23.012; 2020: y = -10.927x + 25.175), indicating that increasing vegetation greenness reduces surface temperature. These findings confirm that vegetation degradation contributes to thermal amplification in the sub-watershed. The study highlights the importance of vegetation conservation for sustainable watershed management.